2020
DOI: 10.1111/dth.14125
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory assessment for the inflammation role in chronic spontaneous urticaria: A clinical study

Abstract: Chronic spontaneous urticaria (CSU) is triggered by unknown causes. We would like to explore the possible effect of hemogram parameters and several biochemical markers on CSU presence and also the severity of the disease. We also aimed to discuss the relationship between CSU and inflammation associated with these values. The study was planned prospectively. We selected patients already diagnosed with CSU who applied to the dermatology outpatient clinic and healthy controls. The patients and the healthy control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…13 However, serum levels of Bil were reported as normal in some other dermatological disorders such as lichen planus and chronic spontaneous urticaria. 8,22 In humans, over half of the antioxidant capacity of blood plasma comes from uric acid. In other words, UA is the most potent antioxidant in the plasma due to its properties to detoxify a wide range of oxidants including hydroxyl radicals, superoxide anion, hydrogen peroxide, and peroxy nitrite.…”
Section: Discussionmentioning
confidence: 99%
“…13 However, serum levels of Bil were reported as normal in some other dermatological disorders such as lichen planus and chronic spontaneous urticaria. 8,22 In humans, over half of the antioxidant capacity of blood plasma comes from uric acid. In other words, UA is the most potent antioxidant in the plasma due to its properties to detoxify a wide range of oxidants including hydroxyl radicals, superoxide anion, hydrogen peroxide, and peroxy nitrite.…”
Section: Discussionmentioning
confidence: 99%
“…Serum irisin levels have previously been investigated in obesity, chronic kidney disease, T2DM, metabolic syndrome, inflammatory disease, and various types of cancer [ 3 , 19 25 ]. Ataseven et al showed significantly higher WBC, NEU, and PLT counts in groups with CSU than in healthy controls, although CRP levels were higher in the healthy control group [ 26 ]. NOD-like receptor protein 3 (NLRP3) mutation was detected and Muckle–Wells syndrome (MWS) was diagnosed in a man with a 15-year history of CSU in a recent case report study.…”
Section: Discussionmentioning
confidence: 99%
“…Irisin, IL-2, IL-3, IF-ɣ, TNF-α concentrations of CU and control groups Ataseven et al showed significantly higher WBC, NEU, and PLT counts in groups with CSU than in healthy controls, although CRP levels were higher in the healthy control group[26]. NOD-like receptor protein 3 (NLRP3) mutation was detected and Muckle-Wells syndrome (MWS) was diagnosed in a man with a 15-year history of CSU in a recent case report study.…”
mentioning
confidence: 97%
“…It is divided into chronic spontaneous urticaria (CSU) which has no known causes and chronic inducible urticarias (CIndU) or physical urticarias triggered by such factors 1 . If autoantibodies or unknown factors trigger the disease, it is named as CSU 2 . CSU usually negatively affects the social relations, sleep quality, work performance, and quality of life (QoL) of the patients 3 .…”
Section: Introductionmentioning
confidence: 99%
“…1 If autoantibodies or unknown factors trigger the disease, it is named as CSU. 2 CSU usually negatively affects the social relations, sleep quality, work performance, and quality of life (QoL) of the patients. 3 CSU can also affect sexual life of the patients.…”
Section: Introductionmentioning
confidence: 99%